Pengaruh Komposisi Hara dan Varietas Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum esculentum Mill.) secara Hidroponik Sistem Substrat - Mardhiah Hayati; Nurhayati Nurhayati; Meina Yulita (Jurnal Agrista, 2011)
The effect of Nutrient Composition and Tomato’s Variety on the Growth and Yield of Tomato (Lycopersicum esculentum Mill.) in Substrate System HydroponicsABSTRACT. This study was aimed at determining nutrient composition and tomato varieties, and the interaction between these two factors on the growth and yield of tamato in substrate system hydroponics. The experimental design used was completely factorial randomized design. There were 2 factors studied, nutrient composition (Nutrisi Hara Spesial/ NHS, Hartuse and Growmore formulas) and tomato’s varieties (Epoch (S-901), Jelita and Donna). Variables observed in this study were plant height, stem diameter, fruit diameter, fruit number and weight of the total fruit crop per plant. The result showed that the nutrient composition significantly affect the plant height at 15 and 30 DAT, stem diameter increment at 15, 30 and 45 DAT, fruit diameter, fruit number and weight of the total fruit crop per plant. The significant effect on plant height 45 days after planting was also found. The best growth and yield of tomato plants were found in nutrient composition of NHS. Tomato’s variety had a very significant effect on plant height at 45 DAT, significantly affected plant height age 30 DAT and the number of fruit per plant. The growth and yield tomato variety was Jelita. There was no significant interaction between nutrient compositions treatment on tomato’s varieties on all the observed variables.